Physical education and health
Physical education and health 2nd edition covers five units. This book is an exploratory and introductory course which leads you to Physical Education and Health Certificate Level I. In this edition units have been revised and new topics are added to make each subject matter more interesting and easier to understand by the students. It aims to inspire learners in striving harder by developing a sense of responsibility and commitment as they go along with the course. Unit 1 provides students with knowledge, skills and behaviors to enable them to achieve a degree of autonomy in developing and maintaining their physical, mental, social and emotional health. Unit 2 discusses the role of sports in physical education to maintain or improve physical ability and skills while providing enjoyment to participants. Unit 3 describes the role of dance in optimizing health. It is not easy for us to change the amount of time we spend sitting down at work without a drastic career switch. That means that the best way we can become more active and start reaping the many benefits that come with that, is for us to engage in more activities outside of work when we get home. Unit 4 presents a significant fragment of recreational activities designated as hobbies for pleasure on a regular basis. Unit 5 present the role of sociological and psychological education in development to shape the behavior and bring some changes.